Identification of Toxoplasma Gondii in The Feces of Domestic Cats in Watukumpul Village, Watukumpul District, Pemalang Regency - Ghofur, Abdul; Wahyu Juniawan, Ivan (INDOGENIUS, 2025)
Background & Objective: Cats can transmit toxoplasmosis, which is caused by the parasite Toxoplasma gondii. Toxoplasmosis can be transmitted from animals to humans and has serious consequences, especially for pregnant women and individuals with weakened immune systems. The sedimentation method is one way to detect the presence of Toxoplasma gondii oocysts in feces by using a solution with a lower specific gravity than the oocysts and utilizing centrifugal force, causing the parasites to settle at the bottom. This study aims to determine whether Toxoplasma gondii is present in the feces of domestic cats in Watukumpul Village, thereby providing useful information for the prevention and control of toxoplasmosis. Method: This study is a descriptive study, where the researcher identifies the presence of Toxoplasma gondii in domestic cat feces that can cause toxoplasmosis. Result: The results of Toxoplasma gondii identification using the sedimentation method on 12 samples of domestic cat feces in Watukumpul Village were all negative (100%). Conclusion: Therefore, based on the results of the identification of Toxoplasma gondii in 12 samples of domestic cat feces in Watukumpul Village, it can be concluded that all (100%) were not infected with Toxoplasma gondii.